Emotional responses to likes and comments regulate posting frequency and content change behaviour on social media: An experimental study and mediation model. (November 2021) - Stsiampkouskaya, Kseniya; Joinson, Adam; Piwek, Lukasz; Ahlbom, Carl-Philip
Abstract: Online photo sharing and the associated engagement from other users, defined as number of likes and comments received for a post, is a key function of modern social media. However, little is known about emotional responses of social media users to the received engagement, and how such responses might drive social media photo sharing. In this study, we present a model of emotional mediation of the effects of social media engagement on posting frequency and content change. To test our model, we conducted a within-subject online experiment with 248 social media users. During the experiment, the participants were exposed to three conditions following a photograph sharing scenario: their usual pattern of engagement, more engagement than expected, and less engagement than expected. In each condition, the participants reported their emotions, estimated the time until their next post, and chose a photo for their next post. The results of the study indicated that high-arousal positive emotions mediate the effects of more engagement than expected on posting frequency. Both high-arousal and low-arousal negative emotions mediate the effects of less engagement than expected on content change. The practical implications for creating effective social media campaigns and improving user experience are discussed. Highlights: A within-subject experimental study on how likes and comments drive photo sharing. Emotions mediate the effects of engagement on posting frequency and content change. Users post more frequently if they feel excited after receiving likes and comments. Users change content if they feel sad after not receiving expected engagement. Likes and comments have direct effects on posting frequency and content change.